2018
DOI: 10.1038/s41536-018-0050-7
|View full text |Cite
|
Sign up to set email alerts
|

Guided genetic screen to identify genes essential in the regeneration of hair cells and other tissues

Abstract: Regenerative medicine holds great promise for both degenerative diseases and traumatic tissue injury which represent significant challenges to the health care system. Hearing loss, which affects hundreds of millions of people worldwide, is caused primarily by a permanent loss of the mechanosensory receptors of the inner ear known as hair cells. This failure to regenerate hair cells after loss is limited to mammals, while all other non-mammalian vertebrates tested were able to completely regenerate these mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 52 publications
0
52
0
Order By: Relevance
“…In a previous study (10), we showed that mutations in smn1 and gemin5 negatively impacted the ability of zebrafish to regenerate different tissues after injury. Regenerative medicine is a rapidly expanding field of science that focuses on replacing or regenerating organs damaged by injury, aging, or degenerative conditions.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…In a previous study (10), we showed that mutations in smn1 and gemin5 negatively impacted the ability of zebrafish to regenerate different tissues after injury. Regenerative medicine is a rapidly expanding field of science that focuses on replacing or regenerating organs damaged by injury, aging, or degenerative conditions.…”
Section: Introductionmentioning
confidence: 84%
“…Our previous large-scale mutagenesis screen showed smn1 and gemin5, two SMN complex members, were essential for tissue regeneration (10). In this study, we expanded our mutagenesis screen to systemically examine the potential role of each of the nine members of the SMN complex in tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations